INCREASING THE STUDENT CREATIVITY IN THE MATHEMATICS LEARNING THROUGH THE IMPLEMENTATION OF AN ACTIVE LEARNING MODEL WITH QUESTION STUDENT HAVE METHOD - Fauzi, Rahmad (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2017)
Classroom action research is aimed to improve students' learning creativity through learning model of Active Learning with Question Student Have method with the material circle. The subject in this research is grade VII-a MTs. Muhammadiyah 22 Padangsidimpuan with consist of students 34 students. The object of the research is to increase students' mathematical creativity through Active Learning model with Question Student Have method. Learning device in this research is the lesson plan, Teacher Handbook, Student Worksheet, Instrument test. The tests are used the validated and reliable test in learning mathematics. From the data analysis is showed that the evaluation result for the cycle I get 64,71%, the cycle II get 82.35%, and for cycle III get 91.18%. The result of student activity observation in cycle I get 54,9%, cycle II get 59,90% and cycle III get 86,70%. Observation on teachers’ competence in managing learning process in cycle I get 73.50%, on the cycle II and the cycle III are increasing between 80% and 3.75%. The Results of students’ response to the first cycle get 89.99%, the second cycle get 92.5% and the third cycle gets 96.43%. Based on the result of this research the Active Learning model with Question Student Have method can increase students' mathematical creativity on the material the circle.